The Demographics, pre-procedure knowledge, and post-procedure experience of the oocyte donation process amongst young females in Northern Nigeria: a cross-sectional study - Anya, Okorie C.; Omoloye, Elizabeth O.; Agbo, Obinna R.; Adesola, Adeyemo J.; Ajayi, Eniola R.; Ubana, Kokei D.; Ohanaka, Adaeze I.; Rathore, Rajni; Rangrej, Shahid B. (International Journal of Research in Medical Sciences, 2024)
Background: Oocyte donation is a third-party treatment employed in assisted reproductive technology where good-quality oocytes obtained from young females are used by females with advanced age, poor ovarian reserve, and poor oocyte quality for in-vitro fertilization. A major challenge facing this treatment option is the availability of donors, and this study was done to ascertain the demographics of donors and their prior knowledge and experience of the process. The aim is to provide information that can be used to improve awareness and execution of the process. Methods: This is a multi-center cross-sectional study that enrolled 154 participants who donated their oocytes between May 1st, 2023, and June 30th, 2024, in five major fertility clinics located in Abuja, Nigeria. Questionnaires were used to obtain data from the donors; the information obtained was analyzed using IBM SPSS Statistics 29.0.1.1. and presented as simple descriptive statistics. Results: Average age was 23.7 years, and 71% of the participants had secondary education as their highest level of education. A total of 45% admitted to having anxieties prior to the procedure, of which 7.3% graded their anxiety as severe. During the procedure, 29.9% experienced symptoms, but only 27.1% stated that they would be willing to undergo the procedure again. Conclusions: Opportunistic health education and adequate pre-procedure counseling are recommended to increase awareness of oocyte donation and improve the experience of the participants.